Pendampingan Edukasi Literasi Keuangan Dan Penerapan Pemasaran Digital Pada Pelaku Usaha Industri Rumahan - Zulfa Zakiatul Hidayah; Prasetyo Hari Sandi; Muhamad Syahwildan; Etty Zuliawati Zed; Erin Soleha (Jurnal Kabar Masyarakat, 2023)
The financial literacy and inclusion index for urban areas in 2022 is 86.73%, for rural areas it is 82.69%. There is a gap of 2.10% between rural and urban areas. Seeing this, it is necessary to pay special attention to outreach and education in rural areas so that the strategy for implementing financial education is to increase the quantity of implementing financial education in rural areas. Especially now that we have entered the era of society 5.o where all transactions use technology. Even though the development of technology is very rapid, there are still many business actors who do not understand the use of information technology (Sugiarto et al., 2022). In this digital era, it is expected to form an information technology, especially in the field of marketing. Business actors, especially Mrs. Asri as the owner of the Serangkai Rasa business herself, said that there is still a lack of socialization of financial literacy itself, this is an obstacle for the community, especially business actors, in keeping abreast of economic developments, especially in the industrial era 4.o where all transactions have been carried out in technology-based businesses. . This service activity can provide positive results for the Implementation of Financial Literacy Education and Digital Marketing for Home Industry Business Actors.